2019
DOI: 10.1111/nmo.13539
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture promotes the gastrointestinal motility of diabetic mice by CNP/NPR‐B‐cGMP and PDE3A‐cGMP signaling

Abstract: Background Electroacupuncture (EA) can promote gastrointestinal (GI) motility of diabetic mice, but the mechanism is not clearly elucidated. Natriuretic peptides (NPs) were related to the diabetes‐induced gut dysfunction of mice, which may be associated with ICC (interstitial cells of cajal). Besides, EA could increase the ICC of diabetic mice. Our aim was to explore whether EA can promote the gut motility by CNP/NPR‐B‐cGMP and PDE3A‐cGMP signaling in diabetic mice, and the relationship between NPs and ICC. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Consistent with previous studies, our results found that PGP9.5 and GFAP decreased in colon tissues of diabetic mice induced by STZ at 16 weeks. Diabetic colonic motility disorder is characterized by abdominal distension and constipation, and its pathophysiological characteristics include decreased colonic tension and contractility, slow peristalsis, and delayed emptying [ 7 , 31 33 ]. Moreover, in our study, we also found that compared with normal mice, the autonomic contractile ability of colonic muscles and the ability to respond to electric field stimulation in diabetic mice were reduced, the intestinal transmission ability was poor, and the fecal water content and frequency of defecation were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, our results found that PGP9.5 and GFAP decreased in colon tissues of diabetic mice induced by STZ at 16 weeks. Diabetic colonic motility disorder is characterized by abdominal distension and constipation, and its pathophysiological characteristics include decreased colonic tension and contractility, slow peristalsis, and delayed emptying [ 7 , 31 33 ]. Moreover, in our study, we also found that compared with normal mice, the autonomic contractile ability of colonic muscles and the ability to respond to electric field stimulation in diabetic mice were reduced, the intestinal transmission ability was poor, and the fecal water content and frequency of defecation were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that the loss of ICCs contributed to the delayed GI motility 32,38 . Our previous and current study have proved both the high‐ and low‐frequency EA could restore impaired ICC in stomach and colon of diabetic rats and mice, resulting in the promotion of GI motility 1,4,5 . Unfortunately, to date, the mechanisms involved were not fully understood.…”
Section: Discussionmentioning
confidence: 60%
“…Electroacupuncture is the combination of the use of traditional Chinese acupuncture and an electrical current, which has been used to treat gastrointestinal disorders for many years. It has been reported that EA at ST‐36 improved the delayed gastric emptying and impaired accommodation in STZ‐induced diabetic rats 1,4,22 . Moreover, the delayed gastric emptying and gastric hypersensitivity were ameliorated by EA in the rodent model of functional dyspepsia 23 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies revealed that CNP/NPR-B and/or NPR-C signaling regulates contractility of the gastric antrum and large intestine 14 17 . It was also suggested that the CNP/NPR-B/cGMP signal may be related to ICC activity 18 20 , and vascular remodeling, and blood pressure 21 28 . Furthermore, CNP is also known to be related to adipocyte metabolism 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%